Problems of intelligence and spirituality under the conditions of modern anthropological crisis - Кадникова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article discusses the causes of the anthropological crisis that emerged in the XX-XXI century under the influence of the global changecaused primarily by scientific and technical progress, it explores new trends in the development of civilization associated with the spiritualand cultural priorities and problems (based on the work of S.B. Krymsky "The human intellect and spirituality of the Millennium").